Violence on America's streets - Brown, Gene. (Brookfield, Conn. : Millbrook Press, 1992)
Photographs and text discuss street crime, gun control, police brutality, and other aspects of crime and violence in modern America.
The violence epidemic -- How we got there -- The causes -- The criminal justice system -- Solutions from Washington.
Includes bibliographical references (p. 62) and index.
Booklist.
Horn Book.
Wilson's Junior High School.
7.2
5-8
Keywords: Crime -- United States -- Juvenile literature; Violence -- United States -- Juvenile literature; Crime; Violence; Crime -- United States; Violence